Fitting Kids In: Children and Inequality in Canada - Shelley Phipps; Lynn Lethbridge (Luxembourg Income Study (LIS), 2002)
This paper adds to the literature on children and inequality a more detailed descriptive analysis of changes in children's experiences of inequality in Canada across time (1973 to 1997) and provides further comparison of the inequality experiences of Canadian children with those of children in 5 other affluent countries (the US, UK, Australia, Germany and Norway). Canada is compared with 3 countries with relatively similar social programs (i.e., the US, the UK and Australia are all from what Esping-Andersen (1990) labels the 'liberal' cluster) as well as with two countries with rather different social programs (Germany is classified as a 'conservative corporatist' state while Norway is 'social democratic'). The focus throughout is upon how changes across time and differences across countries in the family settings of children have affected their experiences of inequality. Microdata from the Survey of Consumer Finance (1973 to 1997) is used to examine where children fit in the Canadian income distribution and how this may have changed over time as family structure, family size, age of parents and labor-force participation of parents have all changed. The position of children in the Canadian income distribution in the late 1990's is also compared to that of children in other affluent countries using microdata from the Luxembourg Income Study with links made to differences across the countries in terms of family structure and size, for example. The remainder of the paper is organized as follows. Section 2 outlines key trends in family settings (e.g., household structure, family size, parental labor-force participation) experienced by Canadian children. Section 3 presents summary measures of inequality among Canadian children and illustrates how children 'fit' into the Canadian income distribution, overall and for specific groups (e.g., children in lone-parent families; children in one- versus two-earner families). Section 4 compares Canadian children's experience of inequality with that of children living in other affluent countries. Section 5 offers conclusions.
Keywords: 330; Einkommensverteilung; Kinder; Kanada